ANTISIPASI KONFLIK TERKENDALI MENJADI KONFLIK RADIKAL PADA DESA PEKRAMAN (TINJAUAN DARI SEGI MANAJEMEN) - Ida Bagus Gede Udiyana; Ni Nyoman Seri Astini (Forum Manajemen STIMI Handayani Denpasar, 2008)
This study analyze the conflict in control become the radical conflict at pekraman village. The aim of this study is (1) Identifying the source of conflict causer (2). Knowing uncontrolled and destroying radical conflict can be occured (3). Approach pattern used can lead the conflict to grow the dynamics in custom countryside and obviate the conflict toward radical and damage.